2022
DOI: 10.1159/000522316
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Acute Kidney Injury in Neonates after Cardiopulmonary Bypass

Abstract: Cardiac surgery-associated acute kidney injury (CS-AKI) in neonates has been associated with poor outcomes. Early detection and intervention of acute kidney injury (AKI) are needed in order to mitigate some of these sequalae. Currently, serum creatinine (SCr) remains the gold standard for AKI diagnosis; however, changes are not seen until days after injury thus delaying the diagnosis. Serum creatinine in neonates varies based on multiple factors such as prematurity, the presence of maternal SCr and renal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Neonates who undergo cardiopulmonary bypass during the surgical correction of congenital heart disease are at significant risk for developing cardiac surgery-associated AKI [ 4 ], which leads to an increase in morbidity and mortality [ 15 , 16 ]. In this prospective observational cohort study, we found that renal rSO 2 did not differ between AKI groups during cardiopulmonary bypass but decreased significantly in proportion to AKI severity during the 60 min after completing the final cardiopulmonary bypass cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates who undergo cardiopulmonary bypass during the surgical correction of congenital heart disease are at significant risk for developing cardiac surgery-associated AKI [ 4 ], which leads to an increase in morbidity and mortality [ 15 , 16 ]. In this prospective observational cohort study, we found that renal rSO 2 did not differ between AKI groups during cardiopulmonary bypass but decreased significantly in proportion to AKI severity during the 60 min after completing the final cardiopulmonary bypass cycle.…”
Section: Discussionmentioning
confidence: 99%
“…в раннем послеоперационном периоде. ОПП, возникающее после операций с применением АИК, связано с повышенной заболеваемостью, смертностью и продолжительностью интенсивной терапии, что отражается в результатах различных исследований [10,11].…”
Section: ключевые слова: врожденные пороки сердца (впс) новорожденные...unclassified
“…4 Intervention can be done by maintaining fluid and electrolyte balance and reducing exposures that trigger nephrotoxicity. 5 Based on data from the National Kidney Foundation (NKF), patients with acute kidney failure are estimated to reach 10% of the human population. Based on data from the Indonesian Ministry of Health, from 2022 until October, acute kidney failure in children in Indonesia reached 304 cases with a mortality rate of 52%.The exact cause of the increase in cases is unknown until now, but it is suspected to be caused by the ethylene glycol (EG) content in children's syrup.…”
mentioning
confidence: 99%